Evaluasi Penerapan Sistem Informasi Rekapitulasi Menggunakan Metode Pieces Framework - Fajar Randi (JURNAL LITBANG KOTA PEKALONGAN, 2022)
The result process of recapilating of the vote count in the elections of simultaneus regional heads and vice regional heads (Pilkada). By using recapitulation information system, it is called a technology based application device that functions to publish the result of vote count as well as in the implementation of the recapitulation of the vote count resul. Considering the use of Sirekap is new thing in the implementation of simultaneus regional elections, then an analysis is needed to quantify the effectiveness and efficiency level by using the frame work system methode that focus on 6 analyzes (Performance, Information and Data, Economy, Control and Security, Efficiency and Service). Data collection is done through a questionare and it is using a descriptive approach. The number of samples is 238 with the validity test resulting in an r-count greater than r-table (0.113) with a significance of 5%. The research results show that the average score as follows performance (2,6), information (3,8), Economy (3,7), Control and Security (4,2), Efficiency (3,2), Service (3,3). Based on the research conducted it could be concluded that the application of information systems and recapitulation in 2020 simultaneus regional elections when refering to the average value indicator in the satisfied category.  Keywords: Sirekap, Information Technology, Pieces Framework